Research on Modern Christians and Non-Church Schools: Focusing on Nankai School - HOU Jie, YAN Tao (Journal of Research for Christianity in China (JRCC), 2025)
In modern China, the emergence of Christian and Catholic church-affiliated schools has sparked significant scholarly interest and yielded a series of research findings. However, some Christians engaged in educational practices at non-church schools, proposing a set of educational philosophies that complemented those of church schools. Together, they advanced the modernization of education in modern China, yet their contributions have not received the attention they deserve. In modern Tianjin, Christian educators like Zhang Boling and Zhang Pengchun collaborated closely with Chinese and foreign staff of the Young Men’s Christian Association (YMCA) and Chinese Christians during their educational practices at Nankai School. Through multifaceted interactions, they endeavored to cultivate well-rounded youth in moral, intellectual, physical, and social development, accumulating valuable historical experience worthy of serious examination. Building upon prior research, this paper centers on Nankai School to explore issues concerning modern Christians and non-church schools. It aims to contribute to the ongoing advancement and development of studies on Christianity and modern education.